Wushu Sports Events - A contribution for an Information Management System Prototype - Ferreira, C.; Oliveira, A. (iSHE-SC 2021 - International Sport, Health and Emerging Technologies Summit Conference, 2021)
In the sports industry, databases play a decisive role in the administration, athlete and team scores, athlete performance analysis, injury epidemiology, allowing to develop injury prevention programs, manage information in sports events and contribute to make the arbitration process and scores more fair and unequivocal. So, it is essential that sports institutions have information systems to optimize the organizational performance of the events they promote. The purpose of this study is to define the functional requirements, together with a team that organizes Wushu tournaments, to design a prototype of an information management system for this type of tournaments. Interviews were conducted with the organizers of these events and the answers were uploaded and analyzed on the Leximancer platform. The results highlighted the main themes and concepts under analysis, and were justified with citations of the participants, associated with them. The main themes that stood out were athletes, information, categories, associations, Wushu and registrations. These themes served as a starting point for, together with the analysis of the concepts that emerged associated with them, to define the main functional requirements for the design of an information management system to support Wushu events. It is expected that this study will be able to give visibility to the need for sports institutions to have at their disposal an information management system that is appropriate to the different modalities. This work contributes, at technological level, with the definition of the main functional requirements to start modeling a prototype for wushu event information management. At the social level, it emphasizes the importance of chinese martial arts for the maintenance of health, whose practice refers to the philosophy of physical education as the fundamental tool to build and maintain a healthy, strong and regenerated body. By speeding up the processes inherent to the organization of sports events, it will become possible to hold more events, mobilize more athletes per event and, consequently, promote sports in society. The present study consists of the requirement gathering phase of a larger project that involves the design and development of an information management system prototype for Wushu events.